A comparison of outcome of ACL reconstruction surgery in between all inside and bioscrew technique - Nik Abdul Adel, Nik Alyani (2018)
INTRODUCTION: Anterior cruciate ligament (ACL) reconstruction has evolved during past decade. All inside technique is introduced aiming for less invasive procedure, bone stock preservation, preservation of tendon at its donor site, better graft positioning and fixation technique. This study is conducted to compare the outcomes of this new technique to the previous bioscrew. MATERIAL AND METHODS: A cross sectional study was conducted in patients with ACL injury treated with ACL reconstruction surgery in Hospital Sultanah Nur Zahirah, Kuala Terengganu and Hospital Kemaman, Terengganu. Functional outcome with International Knee Documentation Committee (IKDC) score, SF-36 quality of life score and time taken to return to normal activities were evaluated at 18 to 24 months post-operative. RESULTS: Forty patient were recruited, 20 in each group. Of this, 37 were male with mean age of 25 ± 6.48 years old. 25 were office worker and the rest were field worker. 37.5% were smoker. Patients in bioscrew technique operated at mean of 21.3 ± 12.6 months after the injury while those in all inside technique at 17.7 ± 11.9 months (p-value 0.35). Mean BMI was 24.58 ± 4.59. The SF-36 score were similar in both groups with p-value 0.59. Both groups have same IKDC score of 82.99 ± 12.55. Mean of time taken to return to normal activity level was 46.3 ± 19.7 weeks which was similar in both groups (p-value 0.943). Re rupture rate were 10% in bioscrew technique and 5% in all inside technique. None of them has any form of infection. DISCUSSION: We produce similar result with study by Lubowitz, Volpi and Benea that reported no significant difference in IKDC score in those two groups studied. IKDC score of 86.5%, 81.3% and 89.7% was reported in all inside technique by Lubowitz, Benea and Schurz respectively. CONCLUSION: The functional outcome, quality of life and time return to normal activity were similar between patients who had biotransfix screw and all inside technique.